2019
DOI: 10.1108/jhti-02-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on tips and sexual harassment vulnerability of hotel employees in Accra, Ghana

Abstract: Purpose The purpose of this paper is to examine the relationship between perceived dependence on tips and vulnerability to sexual harassment (SH) among hotel employees in Accra Metropolis, Ghana. Design/methodology/approach Within a cross-sectional research design, 583 employees from 55 hotels completed self-administered questionnaires. Descriptive statistics, χ2 test of independence, Kruskal–Wallis test were used to analyse collected data. Findings Results of the study reveal that dependence on tips is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Even in case of receiving gratuity from the customers employees directly serve, those with greater reliance on tipping may feel that intervening in CSH and helping the target coworker takes their time and attention away from their own customer service performance, thereby potentially reducing customer satisfaction. Similar to our expectation, recent research has found reliance on tipping to be related to employees' perception that reporting sexual harassment to management for action is risky and that their organization is willing to tolerate workplace sexual harassment (Mensah, 2019). Conversely, when employees have less reliance on tipping, they may consider CSH intervention less costly and risky; in the face of this relatively low cost, empathy may better facilitate bystanders' intervention.…”
Section: Moderators On the Relationship Between Empathy And Bystander...supporting
confidence: 80%
“…Even in case of receiving gratuity from the customers employees directly serve, those with greater reliance on tipping may feel that intervening in CSH and helping the target coworker takes their time and attention away from their own customer service performance, thereby potentially reducing customer satisfaction. Similar to our expectation, recent research has found reliance on tipping to be related to employees' perception that reporting sexual harassment to management for action is risky and that their organization is willing to tolerate workplace sexual harassment (Mensah, 2019). Conversely, when employees have less reliance on tipping, they may consider CSH intervention less costly and risky; in the face of this relatively low cost, empathy may better facilitate bystanders' intervention.…”
Section: Moderators On the Relationship Between Empathy And Bystander...supporting
confidence: 80%
“…McDonald and Charlesworth (2016) reported more than 25% of the Australian female workforce experience sexual harassment. In Sub-Saharan African hospitality workplaces, such as Accra, Ghana Akoku (2019) and Mensah (2019) reported this figure to be 49.4%, 98.8% in Cameroon, 78% in Zimbabwe (Mkono, 2010), and 14% in South Africa (Bowen et al, 2013). Similarly, Dawson et al (2021) pointed out that the surge in sexual harassment in workplaces, with one out of every five men under the age of 35 experiencing sexual harassment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In essence, the literature on the topic can be summarized to fall into the following themes: meaning and prevalence (e.g., Aquino et al, 2014;Ariza-Montes et al, 2017;Page, Pina & Giner-Sorolla, 2016); causes, antecedents and motivation (e.g., Fitzgerald et al, 1997;Mensah, 2019); experience, awareness and perception (e.g., Baltag et al, 2021;Mkono, 2010); consequences (e.g., Park et al, 2022;Jung & Yoon, 2020); gender roles (e.g., Kensbock et al, 2015;Kearney, Rochlen, & King, 2004); and organizational climate, support and management (e.g., Alrawadieh et al, 2022;Dawson, Russen, & Madera, 2021). Despite all these arrays of studies, those into the effects of employees' tolerance behavior on organizational effort are in short supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Workplace SH in hospitality industries was reported by 42% of women in the USA [7], 74.6% of women in 27 European countries [8], 89% of women in Australia [9], 50% of women in the Nordic Region [10], and 60% of women in Taiwan [11]. It is also a significant public health concern in Sub-Saharan African (SSA) hospitality industries such as Accra, Ghana (49.4%) [2,12], Cameroon (98.8%) [13], Zimbabwe (78%) [14], and South Africa (14%) [15].…”
Section: Introductionmentioning
confidence: 99%